A novel loop-mediated isothermal amplification-lateral flow dipstick method for Helicobacter pylori detection - Liu, Wenwen; Lu, Gang; Wang, Yu; Chen, Zhenghong; Gao, Yunyun; Yin, Zhipeng; Wu, Yi; Lv, Xiaoqian; Guo, Pengbo; Zhao, Yinghui (Frontiers in Microbiology, 2023)
To eradicate Helicobacter pylori (H. pylori) and reduce the risk of gastric cancer, a sensitive, specific, convenient, and simple detection method is needed. This study aimed to establish a novel loop-mediated isothermal amplification-lateral flow dipstick (LAMP-LFD) method for H. pylori detection. LAMP primer design software was used to design primers for the conserved sites of the H. pylori ureB gene. A ureB-FIP -labelled biotin was used for LAMP amplification, and FAM -labelled probes specifically hybridised with LAMP amplification products, which were then detected by LFD. In addition, a clinical study was conducted to assess LAMP-LFD in 20 faecal samples. The results of the optimisation indicated that H. pylori could be specifically detected by LFD without cross-reaction with other non-H. pylori bacteria when the LAMP was performed at 65 ℃ for 60 min. The lower limit of the detection method was 102 copies/μL, which was 100 times the sensitivity of Polymerase Chain Reaction (PCR). H. pylori-positive faecal samples were detected by LAMP-LFD in 13/20 patients. In conclusion, a new LAMP-LFD assay has been fully established and confirmed for H. pylori detection. The entire process can be completed in approximately 1.5 h, with the advantages of strong specificity, high sensitivity, and simple operation. This study provides a novel potential method for the detection of H. pylori in the clinical settings of primary hospitals and low-resource countries.